Isótopos Estáveis e Química Iônica da Cobertura Glacial da Ilha do Rei George (Shetlands do Sul, Antártica) como Indicadores de Parâmetros Ambientais - FERRON, FRANCISCO ADOLFO; BERNARDO, RONALDO TORMA; SIMÕES, JEFFERSON CARDIA (Pesquisas em Geociências, 2001)
Hydrogen and oxygen stable isotopes and anionic concentration (sulphates, chlorides and nitrates) in snow and ice from King George Island are presented. Isotopic and chemical composition are preserved in the uppermost part of the ice cap (first meters) providing informations about some environmental parameters as the origin of precipitation and particles (impurities) e its distribution, atmospheric circulation and the physics processes occurring in the ice pack.